Hydroponic Vegetables by Utilizing Beverage Plastic Bottle Waste - Cut Novrita Rizki; Fitriyasni Fitriyasni; Manja Manja; Khaira Ulfi; Mainidar Mainidar (Bulletin of Social Studies and Community Development, 2023)
Abstract: The interest of Gampong Baro residents in farming, the limited space for living , the abundance of plastic  bottle waste  from beverages, and the lack of knowledge  among Gampong Baro residents regarding the processing of plastic bottle waste, have turned plastic  beverage bottles into mere waste without functional value. The existence of  this community service is expected to make the residents of Gampong Baro realize that the accumulated  plastic bottle waste will be difficult to decompose in  the soil  and will have negative  health  impact  if burned. Plastic  bottle waste has highly diverse functions if we understand  to process it. The purpose of this community service is to provide counseling to Gampong Baro residents on how to utilize  plastic  bottle waste, one of which is to use it as a media for hydroponic  vegetable cultivation. The result of this community service is healthy vegetables grown hydroponically using  plastic bottle waste. The purpose of this community service is to reduce plastic bottle waste, enable gardening as a hobby despite limited space. The method used in this community service is the wick system, which is one of the hydroponic methods. The importance of the results of this community service is to inform the residents of Gampong Baro that plastic  bottle waste can be utilized and has  functions  that can yield healthy vegetables, thereby enhancing the economic  value of Gampong Baro residents.    Keywords: waste; hydroponic; vagetable; gampong baro; plastic bottle.